Acute Febrile Illness: A Way to Diagnosis - Bari , Md Shafiqul (Bangladesh Journal of Medicine, 2024)
The evaluation of acute febrile illness (AFI) is a crucial aspect of clinical practice, aimed at identifying the underlying cause and guiding appropriate management. AFI refers to a sudden onset of fever without an obvious source, presenting a diagnostic challenge due to the diverse etiologies involved. The initial AFI assessment includes a thorough history and physical examination to identify potential infectious or non-infectious triggers. Common infectious causes include viral, bacterial, and parasitic pathogens, with region-specific variations influencing epidemiological considerations. Non-infectious etiologies such as autoimmune diseases, malignancies, and drug reactions should also be considered, especially in atypical presentations or refractory cases. Laboratory investigations play a pivotal role in diagnosing AFI and initially, full blood count, routine urine examination, and a chest X-ray will hint at many of the aetiologies. Identification of specific pathogens needs serological tests, nucleic acid amplification, and culture techniques. Blood cultures remain a cornerstone for bacterial infections, while molecular assays offer rapid detection of viral pathogens. Sometimes, special investigations like imaging techniques such as ultrasonogram, echocardiogram or computed tomography scan, and biopsy are needed to evaluate AFI properly. The approach to AFI management is tailored to the suspected etiology, severity of the illness, and patient characteristics. While waiting for diagnostic results, empirical antimicrobial therapy is often started based on clinical suspicion. Microbiological findings and antimicrobial stewardship principles then guide any changes that are made. In conclusion, the evaluation of AFI requires a systematic approach encompassing thorough clinical assessment and targeted laboratory investigations. Timely recognition of potential complications and appropriate interventions are essential to optimize patient outcomes and mitigate the risk of morbidity and mortality associated with AFI. Collaboration between clinicians, microbiologists, and other healthcare professionals is paramount to accurately diagnosing and managing this common clinical syndrome effectively. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 132